2014
DOI: 10.1007/s10571-014-0134-x
|View full text |Cite
|
Sign up to set email alerts
|

Wogonin Prevents Rat Dorsal Root Ganglion Neurons Death via Inhibiting Tunicamycin-Induced ER Stress In Vitro

Abstract: Wogonin is a natural flavonoid isolated from the root of Scutellaria baicalensis Georgi, which has been widely used in various research areas for its anti-oxidant, anti-inflammatory, and anti-cancer activities. It also presents a neuroprotective effect in the brain while encounters stress conditions, but the mechanisms controlling the neuroprotective effect of wogonin are not clear. In this study, we investigated the biomechanism underlying the neuroprotective effect of wogonin on rat dorsal root ganglion (DRG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…To restore ER functioning, signaling in the UPR is initiated by ER trans-membrane proteins, including activating PERK, IRE1, and ATF6 (Lynch et al 2012;Dufey et al 2014). It was previously reported that TUNinduced cytotoxicity in DRG neurons is also associated with activation of the three branches of the UPR Xu et al 2015). We confirmed in our present study that all three branches of the UPR were activated by TUN.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To restore ER functioning, signaling in the UPR is initiated by ER trans-membrane proteins, including activating PERK, IRE1, and ATF6 (Lynch et al 2012;Dufey et al 2014). It was previously reported that TUNinduced cytotoxicity in DRG neurons is also associated with activation of the three branches of the UPR Xu et al 2015). We confirmed in our present study that all three branches of the UPR were activated by TUN.…”
Section: Discussionsupporting
confidence: 89%
“…The process of DRG neuron culture was based on previous studies Xu et al 2015). The cell culture materials and reagents were obtained from Invitrogen (Grand Island, NY, USA).…”
Section: Cell Culturementioning
confidence: 99%
“…Several studies have reported that wogonin protected neuronal death in oxidative stress-induced rat primary cortical neuron [35], and also significantly reduced neuronal death and attenuated brain edema in brain after TBI [27]. In addition, wogonin protected rat DRG neurons from Tunicamycin-induced apoptosis and ER stress as well [20, 21]. Furthermore, wogonin could protect retinal pigment epithelium cells from hydroperoxide-induced apoptosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies in vitro have demonstrated that wogonin could reduce endoplasmic reticulum (ER) stress and apoptosis in Tunicamycin-induced rat dorsal root ganglion (DRG) neurons [20, 21], and suppress lipopolysaccharide (LPS)-induced release of pro-inflammatory cytokines in rat DRG neurons by inhibiting TLR4-NF-κB pathways [22]. In addition, wogonin could suppress LPS-induced release of pro-inflammatory cytokines [23, 24] and reduce migration [25] of microglial cells by inhibiting NF-κB-dependent pathways.…”
Section: Introductionmentioning
confidence: 99%
“…ARPE-19 cells (5x10 4 cells/well) were cultured in 96-well plates for 24 h at 37˚C, then pre-treated with different concentrations of wogonin (0-50 µM) for 24 h, followed by 24 h LPS stimulation. The concentrations of wogonin used to treat ARPE-19 cells were based on the results of previous studies (19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%